Abnormal interhemispheric and intrahemispheric functional connectivity dynamics in drug‐naïve first‐episode schizophrenia patients with auditory verbal hallucinations. Issue 14 (25th May 2022) - Wei, Yarui; Han, Shaoqiang; Chen, Jingli; Wang, Caihong; Wang, Weijian; Li, Hong; Song, Xueqin; Xue, Kangkang; Zhang, Yong; Cheng, Jingliang
Abstract: Numerous studies indicate altered static local and long‐range functional connectivity of multiple brain regions in schizophrenia patients with auditory verbal hallucinations (AVHs). However, the temporal dynamics of interhemispheric and intrahemispheric functional connectivity patterns remain unknown in schizophrenia patients with AVHs. We analyzed resting‐state functional magnetic resonance imaging data for drug‐naïve first‐episode schizophrenia patients, 50 with AVHs and 50 without AVH (NAVH), and 50 age‐ and sex‐matched healthy controls. Whole‐brain functional connectivity was decomposed into ipsilateral and contralateral parts, and sliding‐window analysis was used to calculate voxel‐wise interhemispheric and intrahemispheric dynamic functional connectivity density (dFCD). Finally, the correlation analysis was performed between abnormal dFCD variance and clinical measures in the AVH and NAVH groups. Compared with the NAVH group and healthy controls, the AVH group showed weaker interhemispheric dFCD variability in the left middle temporal gyrus ( p  < .01; p  < .001), as well as stronger interhemispheric dFCD variability in the right thalamus ( p  < .001; p  < .001) and right inferior temporal gyrus ( p  < .01; p  < .001) and stronger intrahemispheric dFCD variability in the left inferior frontal gyrus ( p  < .001; p  < .01). Moreover, abnormal contralateral dFCD variability of the left middle temporal gyrus correlated with the severity of AVHs in the AVH group ( r  = −.319, p  = .024). The findings demonstrate that abnormal temporal variability of interhemispheric and intrahemispheric dFCD in schizophrenia patients with AVHs mainly focus on the temporal and frontal cortices and thalamus that are pivotal components of auditory and language pathways. Abstract : Here, we collected and analyzed resting‐state functional magnetic resonance imaging data for drug‐naïve first‐episode schizophrenia patients, 50 with auditory verbal hallucinations (AVHs) and 50 without AVH (NAVH), and 50 age‐ and sex‐matched healthy controls. Whole‐brain functional connectivity was decomposed into ipsilateral and contralateral functional connectivity, and sliding‐window analysis was used to calculate the interhemispheric and intrahemispheric dynamic functional connectivity density (dFCD). The findings demonstrate that abnormal temporal variability of interhemispheric and intrahemispheric dFCD in schizophrenia patients with AVHs mainly focuses on the temporal and frontal cortices and thalamus that are pivotal components of auditory and language pathways.